OA01.02. Management of infertility subsequent to endometriosis –A study - Sindhu, A (Medknow Publications & Media Pvt Ltd, 2013)
PURPOSE: To explore the efficacy of Ayurvedic intervention in infertility subsequent to endometriosis by retrospective analysis of clinical encounters. METHOD: A female aged 26 years who underwent two laparoscopic aspirations of the chocolate cysts, adhesion detachment for body of uterus and ovaries with kinked tubes was managed with Ayurvedic medicines on an OPD level. RESULT: Within three months, the menstrual cycles became normal and painless. The USG after course of treatment showed no cysts and the adhesions were also not indicated. The same month the patient responded positive to pregnancy test. A full term normal healthy baby girl was delivered after 8 months. CONCLUSION: The management of endometriosis, which is vatiki yoni roga, based on the manifestations in the patient, was given vata pitta hara treatments, the kalayanakagritham in the medication reduced the stress level and the punarnavadi kwatha with chandraprabha vatika and menocalm reduced the inflammatory conditions and reduced pain. Varanadi kwatha was included along the medication to do the kaphamedohara function and this combination worked on the cysts and the patient felt ovulatory cramps. With the vanishing of the cysts sukumaram kwatha and kalyanaka kwathas were added in the medication along with phalsarpis.